Financial reporting as a source of innovation-relevant competitive intelligence - Vincent O'Connell; Naser M. AbuGhazaleh; Garvan Whelan (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In this article, we demonstrate that contemporary financial reporting systems have the capacity to contribute significantly to the generation of innovation-relevant competitive intelligence. This potential arises because, as part of its regular work, the financial reporting system compiles, collects, analyzes, and synthesizes strategically relevant information about (i) complex internal technical processes related to inventions, discoveries, product development, process innovations, and the like; (ii) detailed sales, cost, and profit forecasts; (iii) consumer trends and innovative developments in the firm's markets; (iv) actual and potential competitor actions in the market; and (v) regulatory changes, macro-economic trends, and information about the likely impact of government policies. We argue that this competitive intelligence can, if properly harnessed, lead to better informed discourses and decisions around innovation. Consequently, we highlight the potential-from both academic research and practical perspectives-of financial reporting as an enabler of innovation-relevant competitive intelligence embeddedness within firms.
Keywords: 650; case examples; competitive intelligence; financial reporting; innovation